MAKNA DOA PANGROKAT DALAM TRADISI PETIK LAUT MUNCAR DI DUSUN KALIMATI BANYUWANGI - NFN Annisa (Balai Bahasa Kalimatan Selatan, 2019)
This study aims to describe the meaning of the doa Pangrokat in tradition Petik Laut Muncar inside Kalimati village, Banyuwangi. The meaning there are in the doa Pangrokat is divided into two meanings is the meaning of denotative and connotative meaning by using the theory of semiotics. This research is an ethnography white the semiotic approach. The data sources of this two informant. The results of this study show that difference of meaning. The difference is found in doa Pangrokat is are in trust local society on figures believed. Whereas the denotative meaning there are the doa Pangrokat about matters relating to Islamic.